A Critical Review on the Book The Fantasy Film - Ali Khorashadi; Mohammad Shahba (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The fantasy genre is of the most problematic genres in cinema and has been neglected by cinema adherents for decades. Although the first so-called fantasy works date back to the early years of cinema and the works of George Millis, by the late 1970s, for many reasons, including the relatively high cost of producing such works and the lack of progress in cinematic technology, fewer fantasy works appeared in cinema. One of the important theoretical issues about fantasy works is the confusion of such films with other works of cinema such as horror and science fiction. An accurate definition of the concept of fantasy is problematic; Therefore, considering the creation of brilliant works that carry the attribute of fantasy after the 21st century, and the audience's interest in these works in recent times, as well as the growth of cinematic technology, find specific frameworks to determine the characteristics of fantasy works and distinguish them from other similar works such as science-fiction and horror seem necessary. The Importance of “The Fantasy Film” book by” “Katherine A. Fowkes”, the translation of “Ali Zafar Ghahremani Nejad” is due to the attempt to find answers to these questions and ambiguities that this kind of works have created among cinema people and therefore it is necessary to examine how the author explains the concept of fantasy. This book was published in 2016 by Nashrbidgol in 324 pages.